Preparation and structure of rare earth/thermoplastic polyurethane fiber for X‐ray shielding. Issue 17 (29th December 2018) - Lou, Pengfei; Teng, Xiaobo; Jia, Qingxiu; Wang, Yiqing; Zhang, Liqun
ABSTRACT: Rare earth/polypropylene (PP)/thermoplastic polyurethane (TPU) fibers were prepared by melting spinning with different mass ratios of PP to TPU. Then the rare earth/TPU shielding fiber was obtained by removing the PP matrix phase from the blend fiber using xylene. The fibers were characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X‐ray diffraction (XRD), thermogravimetric analyzer (TG), and scanning electron microscopy (SEM). Short fibers were compression‐molded for the test of lead equivalent. The results showed that the lead equivalent of the rare earth/TPU composite fibers was 0.19 mmPb when the mass ratio of PP/TPU increased to 60/40. At this mass ratio, the X‐ray shielding performance of the fiber was the best. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47435. Abstract :